(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study analyzes the human resources, product portfolio, and distribution channels of Imexpharm Pharmaceutical Joint Stock Company (IMP) in 2023 to evaluate operational efficiency and competitive advantages. Methods: A descriptive and retrospective analysis was conducted using secondary data extracted from audited annual reports, financial statements, and internal corporate documents. Results: The findings indicate that IMP possesses a high-quality workforce of 1,405 employees (an increase of 11.5% compared to 2022), with a strong focus on training and talent retention (retention rate of 89%). The product portfolio is diverse, comprising 333 products, of which beta-lactam antibiotics account for 45% (150 SKUs), along with 11 new marketing authorizations for export to Europe. The distribution network consists of 20 branches, predominantly located in the South (12 branches), achieving 16,000 points of sale in the OTC channel and a 25% revenue growth in the ETC channel. Conclusion: Human resources, product diversity, and distribution channels play pivotal roles in IMP’s business success. The study recommends enhancing R&D investment, expanding the distribution network in the Northern region, and advancing workforce training to optimize competitive efficacy within the Vietnamese pharmaceutical industry.